Culture System for a Closer Biological Contact Between Macrophages and Microparticles - Miyamoto, Haruki; Higuchi, Katsunori; Nakashima, Yuta; Fujiwara, Yukio; Komohara, Yoshihiro; Nakanishi, Yoshitaka (Frontiers in Mechanical Engineering, 2021)
To investigate the effects of microparticles on the immune system, a device was designed for an optimal culture environment. Macrophages phagocytose microparticles and produce inflammatory cytokines. In a culture environment in which macrophages phagocytose microparticles mixed in a culture medium, it remains unclear whether the macrophages can physically access all the microparticles present in the culture medium. In the culturing of fine particles, such as microparticles, it is necessary to devise methods that can realize a close biological contact between the macrophages and the microparticles. To enable macrophages to appropriately phagocytose microparticles, a microchamber with a glenoid hole for cell culturing was designed and manufactured. To clarify the effects of the size, administration amount, and administration time of the microparticles on the production of inflammatory cytokines, a system that can continuously deliver and collect the culture medium was introduced. The results obtained using these systems helped clarify the aforementioned effects. Our study confirms the possibility of employing a system that can optimally adjust the biological contact between macrophages and microparticles in a culture environment.